Difference in the Standard and Novel Lipid Profile Parameters Between Patients With Alzheimer's Disease and Vascular Dementia Stratified by the Degree of Cognitive Impairment - Zaciragic, Asija; Dervisevic, Amela; Valjevac, Amina; Fajkic, Almir; Spahic, Selma; Hasanbegovic, Ilvana; Jadric, Radivoj; Lepara, Orhan (Materia socio-medica, 2022)
Background: Lipids and lipoproteins are significantly involved in maintaining structural and functional components of the human brain and neurons, but their role in the development of Alzheimer's disease (AD) and vascular dementia (VD) remains unclear. Objective: The aim of the present study was to explore the differences in the standard and novel lipid profile parameters in patients with AD and VD, stratified by the degree of cognitive impairment (CI). Methods: Present study included 66 patients with AD, 50 patients with VD, and 60 control subjects. For an evaluation of the global cognitive function the Montreal Cognitive Assessment (M°CA) test was used. In order to distinguish patients with VD from those with AD the Hachinski ischemic score was used. Plasma total cholesterol (TC), high-density lipoprotein -cholesterol (HDL-C), and triglycerides (TG) levels were determined using standard enzymatic colorimetric techniques, whereas the Friedewald formula was used to calculate low-density lipoprotein-cholesterol (LDL-C) levels. The non-traditional lipid indices such as TG/HDL-C,TC/HDL-C, and LDL-C/HDL-C ratio were separately calculated. The differences between the groups were analyzed with the Kruskal Wallis test followed by the Mann-Whitney test or with ANOVA followed by the Tuckey posthoc test. Results: Results of the conducted study have found that the patients in AD group with moderate CI and patients in AD group with severe CI exhibited significantly lower levels of serum TC, TG, LDL-C, VLDL-C, Non-HDL-C, atherogenic index, TG/HDL-C, TC/HDL-C and LDL-C/HDL-C compared to cognitively normal control subjects. Moreover, patients in VD group with severe and moderate CI had significantly lower level of TG compared to control group of subjects. Our results have also shown that patients in AD group with moderate CI had significantly lower level of TC, TG, LDL-C, Non-HDL-C, atherogenic index, TG/HDL-C, TC/HDL-C compared to VD patients with moderate CI. In addition, patients in AD group with severe CI had significantly lower level of TC, LDL-C, Non-HDL-C and TC/HDL-C compared to VD patients with severe CI. Conclusion: The results of this study have shown dysregulation of lipid metabolism in AD and VD patients with different degree of CI. In both moderate and in severe CI, patients with AD had lower levels of majority of standard and novel lipid parameters compared to patients with VD. Further larger prospective studies are required to elucidate the accuracy of standard and novel lipid parameters in the assessment of different degree of CI in AD and VD.